Evaluation of Intermolecular Free Length in Binary Liquid Mixtures - Saxena, M.C.; Tripathi, Ashutosh; Saigal, Minu (Asian Journal of Chemistry, 2010)
Intermolecular free length has been evaluated in the binary mixture of cyclohexane-benzene, cyclohexane-toluene and cyclohexane- p-xylene at 30°C using three different approaches. Relative merits of every approach have been accessed. Furthermore, the study has been extended to obtain excess free length and to discuss intermolecular interaction within the components of the mixture.